2016
DOI: 10.1038/srep36553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Acceptability of Different Auxiliary Drugs in Pediatric Sevoflurane Anesthesia: A Network Meta-analysis of Mixed Treatment Comparisons

Abstract: Emergence agitation preventive medicine should be combined with pediatric anesthesia because of the high frequency of emergence agitation. However, it is challenging to determine the most appropriate medication that can be introduced into pediatric anesthesia for the sake of emergence agitation prevention. We reviewed and retrieved the data from PubMed and Embase. Various medications were assessed based on several endpoints including Emergence agitation outcomes (EA), postoperative nausea and vomiting (PONV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…A network meta‐analysis examined seven auxiliary medications that were administered along with pediatric sevoflurane anesthesia for the reduction of POV and emergence agitation. The result showed that clonidine exhibited the highest cumulative ranking probability for reducing POV when compared to other medications . However, these patients received different types of surgical operations, and some common prophylactic antiemetic drugs were not examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A network meta‐analysis examined seven auxiliary medications that were administered along with pediatric sevoflurane anesthesia for the reduction of POV and emergence agitation. The result showed that clonidine exhibited the highest cumulative ranking probability for reducing POV when compared to other medications . However, these patients received different types of surgical operations, and some common prophylactic antiemetic drugs were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that clonidine exhibited the highest cumulative ranking probability for reducing POV when compared to other medications. 24 However, these patients received different types of surgical operations, and some common prophylactic antiemetic drugs were not examined. On the other hand, high-level evidence supporting premedication on POV prevention in pediatric ophthalmology surgery is scarce.…”
Section: Strengths and Weaknesses Concerning Other Studiesmentioning
confidence: 99%
“…It is known that sevoflurane is the most frequent culprit agent in pediatric cases with postoperative agitation. [6][7][8] As reported by Son et al, induction of anesthesia with thiopental may decrease the frequency of postoperative agitation when compared with sevoflurane; however, a combination of propofol and ketamine may be the most effective.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine acts as an alpha2‐adrenoceptor agonist and is approved for the treatment of hypertension, as an adjunct for epidural pain management, and for the management of pediatric attention deficit hyperactivity disorder. Clonidine is used off‐label in pediatric anesthesia for several indications, for example, treatment of acute pain, sedation in intensive care, treatment and prevention of postoperative agitation and to counter withdrawal symptoms in children after long‐term sedation 1‐5 . Pharmacokinetic knowledge is helpful for optimal clinical use, and clonidine pharmacokinetics in children has been investigated for oral, 6 intranasal, 7 rectal, 8 epidural, 9,10 and intravenous administration 11‐13 .…”
Section: Introductionmentioning
confidence: 99%